Effect of Zwitterionic Additive on Electrode Protection through Electrochemical Performances of Anatase TiO2 Nanotube Array Electrode in Ionic Liquid Electrolyte - Roganović, Aleksandra; Vraneš, Milan; Cvjetićanin, Nikola; Chen, Xiaoping; Papović, Snežana (International journal of molecular sciences, 2023)
In this work, a functionalized zwitterionic (ZI) compound 1-butylsulfonate-3-methylimidazole (C1C4imSO3) was synthesized and tested as an additive to LiTFSI/C2C2imTFSI ionic liquid-based electrolytes for lithium-ion batteries. The structure and purity of C1C4imSO3 were confirmed by NMR and FTIR spectroscopy. The thermal stability of the pure C1C4imSO3 was examined by simultaneous thermogravimetric–mass spectrometric (TG–MS) measurements and differential scanning calorimetry (DSC). The LiTFSI/C2C2imTFSI/C1C4imSO3 system was tested as a potential electrolyte for lithium-ion batteries by using anatase TiO2 nanotube array electrode as the anode material. This electrolyte with 3% C1C4imSO3 showed significant improvement of lithium-ion intercalation/deintercalation properties, such as capacity retention and Coulombic efficiency compared to electrolyte without additive.